2018
DOI: 10.1111/cdoe.12376
|View full text |Cite
|
Sign up to set email alerts
|

Parental psychosocial factors and childhood caries prevention: Data from an American Indian population

Abstract: Prevention of early childhood caries in American Indian children has proved to be especially challenging. Some of the measures identified in this report may suggest promising directions to prevention through approaches that build on competencies and skills to be learned and used within a context more broadly focused on parenting and management of health and family challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
0
17
0
2
Order By: Relevance
“…We speculate that issues of perceived severity, barriers, and consequences of the problem may play a role in these responses. Furthermore, psychosocial factors-such as oral health locus of control, sense of coherence, stress, and fatalistic attitudes-could be underlying factors that influence the participant's response to a behavior change intervention such as MI (Albino et al 2018). These factors may offer valid explanations why MI interventions are not successful in one group or condition but work for another.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that issues of perceived severity, barriers, and consequences of the problem may play a role in these responses. Furthermore, psychosocial factors-such as oral health locus of control, sense of coherence, stress, and fatalistic attitudes-could be underlying factors that influence the participant's response to a behavior change intervention such as MI (Albino et al 2018). These factors may offer valid explanations why MI interventions are not successful in one group or condition but work for another.…”
Section: Discussionmentioning
confidence: 99%
“…The nominal associations between OHF and dmft/DMFT and child age are of clinical interest for the dental practitioner and are potentially of interest for further study. OHF may be a cause of caries – the less control a caregiver perceives over caries, the less preventive care or behavior the family may adopt, and the worse the disease may become for the child 31,53 . Conversely, caries may be a cause of OHF – the worse disease a child has, the less control a caregiver may feel over the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of children identified as American Indian, parents with no caries experience had higher oral health knowledge, better caries‐prevention habits, and were more likely to perceive internal locus of control. While most children ultimately developed caries, caries progression (measured by increase in decayed, missing, and filled surfaces) was less than that of children of fatalistic parents 31 . Educational intervention decreased fatalistic views in a study of mothers in Turkey 33…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Miller and Rollnick assert that for an individual to change, they must feel both confident in their ability to change and believe change is of value to them [16]. Recent research is steering us in the direction of developing interventions focused on bolstering psychosocial strengths that support parents in achieving optimal oral health for themselves and their children [24][25][26][27]. Albino et al assert, "when a child's oral health is part of a meaningfully organized life, and financial stability is great enough to support their efforts, caregivers are able to ensure their children's oral health to a greater degree [25].…”
Section: Discussionmentioning
confidence: 99%